Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Tracking the Creative Process in Music Second International Conference, 2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique